Differential effects of NSAIDs on amyloid β1-42 peptide aggregation - Atheer Al-Zurfi; Harmesh Aojula; Jeffrey Penny (University of Huddersfield Press, 2019)
Alzheimer's disease (AD) is the most common cause of dementia and one of the great health-care challenges of the 21st century. The disease is characterised by extracellular aggregation of the amyloid beta (Aβ1-42) peptide within the brain, with subsequent formation of plaques leading to dementia. Currently, there is no cure for AD with only symptomatic therapies available which have demonstrated no, or limited, efficacy. Current pharmacologic studies into AD have focused principally on the development of disease-modifying therapies that can slow the progression of AD. Targets of these investigational agents include Aβ1-42 production, aggregation, and clearance. The ability of non-steroidal anti-inflammatory drugs (NSAIDs) to influence Aβ1-42 aggregation was assessed using the thioflavin-T spectrofluorimetric assay. Mefenamic acid and flufenamic acid both significantly reduced Aβ1-42 aggregation in vitro; however ibuprofen and naproxen had no significant effect on aggregation. These studies highlight that NSAIDs may have potential for helping manage or treat AD.